Wykorzystanie benchmarkingu i outsourcingu w zakładzie opieki zdrowotnej - Zaleska, Beata (Benchmarking and outsourcing in medical health centres, 2008)
Benchmarking and outsourcing belong to management methods which, when applied systematically, improve functioning conditions of companies, including health care centres. These methods have the following advantages: they improve effectiveness, lower costs, improve quality of services provided and, at the same time, help achieve a better position on a competing market of medical services. This paper presents the essence, aim, and methods of implementation of benchmarking and outsourcing in health care centres.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 474-478